2013
DOI: 10.3109/07357907.2013.830734
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum Angiopoietin-1 in Malignant Peritoneal Mesothelioma

Abstract: We have previously reported that angiopoietin-1 was correlated with pulmonary fibrosis. Here, we investigated the serum levels of angiopoietin-1 in patients with malignant peritoneal mesothelioma, which originate from mesenchymal cells similar to lung fibroblasts. We showed that patients with peritoneal mesothelioma had significantly higher serum levels of angiopoietin-1 in comparison with a population with a history of asbestos exposure without peritoneal mesothelioma, and the Kaplan-Meier method revealed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The selected differentially expressed proteins in the present study have been reported be linked to tumor development and progression in several types of cancer (11)(12)(13)(14). However, their association with HCC is, by contrast, rarely reported.…”
Section: Association Of Dysregulated Proteins With Clinical Hccmentioning
confidence: 67%
“…The selected differentially expressed proteins in the present study have been reported be linked to tumor development and progression in several types of cancer (11)(12)(13)(14). However, their association with HCC is, by contrast, rarely reported.…”
Section: Association Of Dysregulated Proteins With Clinical Hccmentioning
confidence: 67%
“…Ang-1 expression quantified by mRNA was shown to correlate with tumor vascularity in previous reports [24]. In addition, circulating levels of Ang-1 have demonstrated prognostic correlation in other cancers, such as cervical, peritoneal mesothelioma, and nasopharynx and larynx carcinomas [4749].…”
Section: Discussionmentioning
confidence: 90%
“…Angiopoietin-1 has been proposed to be a useful prognostic marker in malignant mesothelioma with important roles in tumor growth [27]. In addition, mesothelioma patients have shown higher serum levels of angiopoietin-1 compared to patients with benign conditions [28].…”
Section: Discussionmentioning
confidence: 99%